Green Synthesis of Silver Nanoparticles using Cultivar Nendran Leaf Extracts and Evaluation of Their Antinemic Activities Against Pratylenchus coffeae (Indian Journal of Nematology, 2024)
The Physio-chemical behaviour, silver uptake, growth inhibition and the mechanism of toxicity of plant- mediated AgNPs against the nematode Pratylenchus coffeae was investigated. The current study revealed the effect of variables such as concentration, pH, mixing ratio of the reactants and interaction time. The size and morphology of AgNPs were analysed by using Ultraviolet-Visible (UV-vis) Spectroscopy, Fourier Transform Infrared (FTIR) Spectroscopy, X-Ray Diffractometry (XRD), Zeta potential and Scanning Electron Microscopy (SEM). The nanoparticles have an average size ranging between 40 to 70 nm and are more or less spherical in shape as determined by SEM. When Pratylenchus coffee was exposed to AgNPs in water at 40 to 100 ìg/ml, >99% nematodes became inactive in 24 hr. This is the first report of silver nanoparticles synthesis using the Nendran Sigar leaves for the management of nematodes (Pratylenchus coffeae) as an alternative to chemical nematicides.